A Novel Method for Target Navigation and Mapping Based on Laser Ranging and MEMS/GPS Navigation. (28th June 2014) - Cheng, Jianhua; Landry, Rene; Chen, Daidai; Guan, Dongxue
Abstract : Making the sensor rigidly mounted in the target is the common characteristic of conventional navigation system. However, it is difficult or impossible to realize that for special applications such as the positioning of hostile aircraft. A novel new algorithm for target navigation and mapping is designed based on the position, attitude, and ranging information provided by laser distance detector (electronic distance measuring, LDS) and MEMS/GPS navigation, which can solve problem of the target navigation and mapping without any sensor in the target. The detailed error analysis shows that attitude error of MEMS/GPS is the main error source which dominated the accuracy of the algorithm. Based on the error analysis, a calibration algorithm is designed so as to improve the accuracy to a large extent. The result shows that, by using this new algorithm, the performance of target positioning can be efficiently improved, and the positioning error is less than 2 meters for the target within 1 kilometer range.